Venetian Walls of Nicosia: Between Kyrenia Gate - Barbaro Bastion - Ongul, Zehra (Univ Politecnica Valencia, 2020)
Nicosia today has the characteristics of being the only divided city in Europe. By examining the inside of the walls, one observes that the structure of the city is determined by the circular plan of the walls that were constructed during the Venetian period. There are 11 bastions on the walls and three Venetian gates, namely Kyrenia Gate, Famagusta Gate and Paphos Gate, were originally designed to allow entrance to the city that is encircled by the walls. Nicosia continued to be the islands capital which has fallen under Ottoman rule in between 1571-1878. In the period of British occupation 1878-1960, as a result of the increasing population, the city of Nicosia overflew the walls and developed by spreading beyond the city walls and 8 new passages were opened. The organic fabric of the walled city, with the establishment of buffer zones after the peace operation of 1974, resulted in the division of the island that divided the capital city into two. In 1931, because of the increased vehicle needs through the north side, the walls around the Kyrenia Gate (Porta del Proveditore) were trimmed and designed as a single monumental building. Between Kyrenia Gate and Barbaro bastion wall height is lower than the existing. Public lavatory and 9 small shops were inserted. Sitting steps were designed on the walls and two stairs were constructed to reach these area. To give an access from the moat to the inner city there is a passage. In this context, identifying changes of the Kyrenia Gate-Barbaro bastion site, during this historic period, is the main goal of this study. Decisions with regard to these walls and observations to be made on right places to determine the changes are main focuses of the study.
International Conference on Fortifications of the Mediterranean Coast (FORTMED) -- NOV 04-06, 2020 -- ELECTR NETWORK
Keywords: Venetian walls; Nicosia; history; Cyprus